2022
DOI: 10.3390/ijerph19116929
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Nurses’ Perceptions of Diabetes Self-Management in Oman: A Qualitative Study

Abstract: Patient-centered care enhances diabetes self-management; however, the primary care nurse’s role in promoting diabetes self-management within a patient-centered care model is unexplored. This study investigated the perceptions of Omani patients with type-2 diabetes and their clinic nurses on the nurses’ role in promoting diabetes self-management within a patient-centered care approach. The thematic analysis of the data from individual interviews with patients (n = 24) revealed two themes: patients experienced “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Patient-centeredness is characterized by utilization of a bio-psycho-social perspective, which means focusing on patients and honoring their preferences as a holistic being, rather than adopting a biomedical perspective that focuses on the disease ( 14 ). The shift from a biomedical model to a patient-centered care model may necessitate more effective patient engagement, collaboration on an individual care plan, and motivation of patients to adopt self-management behaviors ( 15 ). Therefore, PCC is characterized as a care that is tailored to the patients' specific needs, values, and preferences ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patient-centeredness is characterized by utilization of a bio-psycho-social perspective, which means focusing on patients and honoring their preferences as a holistic being, rather than adopting a biomedical perspective that focuses on the disease ( 14 ). The shift from a biomedical model to a patient-centered care model may necessitate more effective patient engagement, collaboration on an individual care plan, and motivation of patients to adopt self-management behaviors ( 15 ). Therefore, PCC is characterized as a care that is tailored to the patients' specific needs, values, and preferences ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study from UK has shown that people with diabetes have been disproportionately affected by COVID-19, with growing evidence of higher mortality and morbidity 25 . Literature has reported geriatric age, diabetes mellitus, hypertension and obesity significantly increase the risk of hospitalization and death in COVID-19 patients 26,27 .…”
Section: Discussionmentioning
confidence: 99%